Analisis Faktor Penyebab Ancaman Baby Boom Pandemi Covid-19 Kecamatan Cimanggis Jawa Barat - Elvada Sukma Novita; Winarno Winarno (Universitas Prof. Dr. Hazairin, S.H, 2022)
In the COVID-19 pandemic, especially in Cimanggis District, there was a high increase in the birth rate. The treat of this baby boom can cause factors consisting of health factors, population factors, economic factors, geographical factors, sosiologis factors as well as psychological factors. The purpose of this study is to educate the public about the consequences of the impact of the baby boom and limit the number of children in couples of childbearing age. The intended research is descriptive with the method of literature study. Ths research technique is by collecting some information from books and the internet from several journal searches with Google Scholar which uses the keyboard “baby boom during the COVID-19 pandemic” and then selecting several journals. Based on analytical considerations, researchers described the number of birth rates during the covid-19 pandemic that caused a high increase and explained the factors of the baby boom threat. For this reason, sometimes the public knows about the threat of the baby boom and how overcome it and BKKBN must provide socialization to the community about the threat of the baby boom.